Manajemen UMKM Dan Strategi Komunikasi Pemasaran Pada Usaha Katik Sate Dan Canang Di Banjar Karya Sidhadharma - Yasa, I Komang Widya Purnama; Aryawati, Ni Putu Ari; Mahardika, I Made Ngurah Oka; Sukendri, Nengah; Wibawa, I Gede Jaya Satria; Pancawati, Ni Luh Putu Anom; Tamara, Ni Wayan Kartika Khaecylia (Dharma Sevanam : Jurnal Pengabdian Masyarakat, 2023)
Community service provides guidance and counseling and helps improve the expertise and skills of human resources so that they can advance in national development growth accompanied by the development of information technology at this time to increase community economic growth. Banjar Karya Sidha Dharma, Karang Pangsor Hamlet, West Pemenang Village, Pemenang District, North Lombok Regency has a business opportunity in producing katik sate as a creative economy based on village resources. Knowledge in fostering financial management of Micro, Small, and Medium Enterprises, as well as marketing communication strategies, aims to make these businesses have sustainable progress in increasing economic power and people's welfare